Spatial Allocation for the Development of Tourism Support Facilities in Ambarawa District, Semarang Regency - Jihan Shonia Pardcipta; Reny Yesiana (Jurnal Planologi, 2026)
Tourism plays a significant role in supporting regional economic growth, yet its development must operate within certain limits to ensure sustainability. This study seeks to develop a spatial allocation plan for tourism-supporting facilities in Ambarawa District. A mixed-method approach was applied, combining qualitative descriptive analysis with quantitative spatial analysis using Geographic Information Systems (GIS). The results identify 595.16 hectares of land suitable for developing various supporting facilities, including accommodations, minimarkets, souvenir centers, eateries, the Serabi Ngampin culinary hub, ornamental plant and flower markets, MSME centers, and parking areas. The study’s contribution lies in its integration of spatial analysis with stakeholder insights, bridging spatial and non-spatial perspectives in tourism planning. The findings underscore the need for stronger alignment between tourism planning and spatial planning instruments, the prioritization of facility provision based on locally identified needs, and the enhancement of community participation. Moreover, effective land-use control is essential to safeguard environmental quality and support sustainable tourism development.Keywords: tourism, spatial planning; land suitability; tourism facilities; GIS Pariwisata merupakan salah satu sektor yang potensial dalam meningkatkan pendapatan daerah. Meskipun demikian, pengembangan pariwisata harus mempertimbangkan keberadaan batasan-batasan agar tetap menerapkan prinsip berkelanjutan. Penelitian ini bertujuan menyusun rencana alokasi ruang untuk fasilitas penunjang pariwisata di Kecamatan Ambarawa. Metode penelitian yang digunakan adalah campuran antara analisis deskriptif kualitatif dan analisis spasial kuantitatif berbasis Sistem Informasi Geografis (SIG). Hasil penelitian menunjukkan bahwa terdapat 595,16 hektare lahan yang dapat digunakan untuk pengembangan fasilitas penunjang pariwisata, yang mencakup: akomodasi, minimarket, pusat souvenir, tempat makan, sentra kuliner Serabi Ngampin, pasar tanaman hias dan bunga, pusat UMKM, serta area parkir. Kebaruan penelitian terletak pada integrasi analisis spasial dengan masukan pemangku kepentingan, yang menghubungkan perspektif spasial dan nonspasial dalam perencanaan pariwisata. Temuan ini menegaskan pentingnya penyelarasan perencanaan pariwisata dengan instrumen tata ruang, prioritas penyediaan fasilitas sesuai kebutuhan lokal, serta peningkatan partisipasi masyarakat. Selain itu, pengendalian pemanfaatan lahan diperlukan untuk menjaga kelestarian lingkungan.Kata kunci: pariwisata, penataan ruang, ketersediaan lahan, fasilitas penunjang pariwisata; SIG